2021
DOI: 10.1016/j.jmig.2020.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Reproductive Outcomes Following Surgical Management of Congenital Anomalies of the Cervix: A Systematic Review

Abstract: The purpose of this systematic review was to evaluate surgical treatment for malformations of the cervix in terms of short-and long-term postoperative function and relevant reproductive outcomes. Data Sources: International Prospective Register of Systematic Reviews (ID No CRD42019128899). Electronic databases were searched for eligible studies up to October 2019 on Medline/PubMed (1966−2019), Scopus/Elsevier (1950−2019), and Google Scholar (up to 2019. Search terms included "congenital cervical malformations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…In a review article published in 2021, it is reported that 249 cases of cervical malformations were managed by different techniques of conservative surgeries and resulted in successful outcome by achieving menstruation in 228/249 patients (91.6%). Regarding fertility, 30 pregnancies (12.0%) were reported: 17 of 155 patients with cervical agenesis (11.0%) and 13 of 71 patients with cervical obstruction (18.3%) [8]. Unfortunately, in this review article, there was no information whether pregnancies occurred naturally or not and no information about the difficulties of the ART if used.…”
Section: Discussionmentioning
confidence: 92%
“…In a review article published in 2021, it is reported that 249 cases of cervical malformations were managed by different techniques of conservative surgeries and resulted in successful outcome by achieving menstruation in 228/249 patients (91.6%). Regarding fertility, 30 pregnancies (12.0%) were reported: 17 of 155 patients with cervical agenesis (11.0%) and 13 of 71 patients with cervical obstruction (18.3%) [8]. Unfortunately, in this review article, there was no information whether pregnancies occurred naturally or not and no information about the difficulties of the ART if used.…”
Section: Discussionmentioning
confidence: 92%
“…Patients with cervical and vaginal aplasia are more likely to have upper genital tract lesions, which may affect the possibility of natural conception to some extent, so assisted reproductive techniques can be suggested appropriately. 8,33,34 One of the limiting factors is that congenital cervical and vaginal aplasia is a rare malformation, so the sample size was small. Another limitation is that the data in this study only reflected the current psychological states of the patients and could not reflect their long-term depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with cervical and vaginal aplasia are more likely to have upper genital tract lesions, which may affect the possibility of natural conception to some extent, so assisted reproductive techniques can be suggested appropriately. 8 , 33 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…Utero-vaginal and utero-neovaginal anastomoses have good outcomes. Creation of neo-cervix is associated with poorer outcomes followed by use of full-thickness skin graft for creating a neovagina [36 ▪ ].…”
Section: Cervical Surgerymentioning
confidence: 99%